INTEGRATION OF TECHNOLOGIES IN MODERN PEDAGOGY - Nurullaeva Laylо Sayfullaevna (Web of Journals Publishing, 2025)
This article examines the issues of technology integration in modern pedagogy. It analyzes the impact of digital tools and educational technologies on teaching methods, learning processes, and student engagement. The paper discusses various forms of technological integration, including online learning platforms, interactive digital resources, and AI-based educational tools. Emphasis is placed on the role of teachers in adapting to technological advancements and the importance of professional development. The article also highlights challenges and prospects associated with the effective use of technology in educational environments. Modern pedagogy faces many challenges and problems that require careful analysis and the search for effective solutions. In a rapidly changing world, where technologies and social conditions are constantly evolving, educational systems must adapt to new realities.
Keywords: integration, educational technologies, students, modern pedagogy